2015
DOI: 10.3390/ijms160612925
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrospun Gelatin Fibers Alignment on Schwann Cell and Axon Behavior and Organization in the Perspective of Artificial Nerve Design

Abstract: Electrospun fibrous substrates mimicking extracellular matrices can be prepared by electrospinning, yielding aligned fibrous matrices as internal fillers to manufacture artificial nerves. Gelatin aligned nano-fibers were prepared by electrospinning after tuning the collector rotation speed. The effect of alignment on cell adhesion and proliferation was tested in vitro using primary cultures, the Schwann cell line, RT4-D6P2T, and the sensory neuron-like cell line, 50B11. Cell adhesion and proliferation were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 58 publications
5
85
0
Order By: Relevance
“…Filaments or fibers have been made of synthetic polymers -like polypropylene (PP) [79], polycaprolactone (PCL) [80], poly-L-lactide (PLLA) [71], poly(acrylonitrile-comethylacrylate (PAN-MA) [48,70] -and natural polymers (e.g. gelatin [63] and chitosan [81]).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Filaments or fibers have been made of synthetic polymers -like polypropylene (PP) [79], polycaprolactone (PCL) [80], poly-L-lactide (PLLA) [71], poly(acrylonitrile-comethylacrylate (PAN-MA) [48,70] -and natural polymers (e.g. gelatin [63] and chitosan [81]).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of topography on cells of neuroglial phenotype has been studied mainly on dissociated primary Schwann cells [58 62], but there are few studies using Schwann cell lines, like RT4-D6P2T [63] and CRL-2765 [64]. Studies on the cellular response of astrocytes on micropatterned substrates remain limited [65,66].…”
Section: Cell Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are comparable with other literature reports where the nanofibrous scaffolds showed lower proliferation rates of Human embryo skin fibroblasts (Duan et al, ) and neural stem cells (Christopherson, Song, & Mao, ) than the TCPS control. Gnavi et al () reported that aligned nanofibers have shown that SCs (RT4‐D6P2T) proliferated more slowly than under TCPS control conditions. It may be attributed to the fact that nanofibrous scaffolds promote better cell spreading and extension compared with the TCPS control, which reduces the space available for the new cell adhesion and thus lower proliferation rates.…”
Section: Discussionmentioning
confidence: 99%